1979
DOI: 10.1029/gl006i004p00226
|View full text |Cite
|
Sign up to set email alerts
|

The role of water content in the magnetization of sediments

Abstract: We have developed a new experimental procedure in order to study the role of water content in the acquisition of post‐depositional detrital remanent magnetism by a sediment. The procedure leads to the determination of the magnetic direction recorded by a sediment as a function of the water content present when that sediment experiences a change in the direction of an applied magnetic field. Experiments with a variety of sediments indicate that in most cases, regardless of the water content, the sediment does n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1980
1980
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…The samples were measured in the magnetometer again and were weighed again to allow calculation of the water content. Water content was estimated following the definition of Verosub et al (1979) where: H 2 O% = ((Mass total -Mass dry )/Mass dry ) x 100%. In many cases, water ponded above the sediment surface in the plastic cubes used to hold the samples, so H 2 O% is not a true measure of water content in relation to sediment pore space.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The samples were measured in the magnetometer again and were weighed again to allow calculation of the water content. Water content was estimated following the definition of Verosub et al (1979) where: H 2 O% = ((Mass total -Mass dry )/Mass dry ) x 100%. In many cases, water ponded above the sediment surface in the plastic cubes used to hold the samples, so H 2 O% is not a true measure of water content in relation to sediment pore space.…”
Section: Methodsmentioning
confidence: 99%
“…The NRM/ARM ratio for such samples is low (~0.1-0.2) because of the inefficient alignment of magnetic particles (Figure 4.8d). As discussed above, the water content definition of Verosub et al (1979) is not a true measure of water content in relation to sediment pore space; the high H 2 O% values indicate that the sample was a wet slurry. Despite this definition, there is a key change in the magnetic recording quality at H 2 O% = 40-50%.…”
Section: Nrm Recording Fidelity From Re-deposition Experimentsmentioning
confidence: 99%
“…The sediments redeposited in the laboratory sometimes show that the amount of remagnetization gradually decreases in drying (Verosub et al, 1979;Barton et al, 1980;Payne and Verosub, 1982). The redeposition experiments of synthetic and natural sediments by Hamano (1980) indicated that magnetic particles are locked also during the compaction and result in the growth of the post-depositional DRM.…”
Section: Introductionmentioning
confidence: 99%
“…Verosub (1977) attempted to elucidate the natural state of the DRM by applying a constraint of the critical water content and by taking account of physical processes of the bioturbation and gravitational compaction. According to the experiment by Verosub et al (1979), remagnetization after the deposition, namely the post-depositional DRM, takes place only for a water content higher than a critical value, but stirring the sediment like the bioturbation can generate remagnetization of the sample. Barton and McElhinny (1979) and Barton et al (1980) support this conclusion from their experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on the acquisition mechanism of the remanences in sediments have revealed the importance of the post-depositional process on though the relative importance of the process depends on the sediment properties (BLOW and HAMILTON, 1978;VEROSUB et al, 1979;BARTON and MCELHINNY, 1979). The effect of the particle interaction is much more important in the postdepositional process than in the process while the particles are floating in water.…”
Section: Introductionmentioning
confidence: 99%